(untitled) (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2024)
The purpose of this article is to show how Isaac Rosa in Tiza Roja (2020) —a collection of fifty short stories— combines some narrative devices with those of the chronicle to represent the crisis that from 2008-2009 up to nowadays have been affecting Spain. He does so to emphasize the effects of crisis in individuals that occupy quite a marginal position in Spanish society. In that way he can create some counter-discourses that, defying the dominant vision of media, draw the attention on a bunch of «histories of life» capable of breaking the silence and involving the reader, compelling him to be aware of the necessity to act as a collective subject in the fight against capitalism.